2007
DOI: 10.5194/acp-7-5519-2007
|View full text |Cite
|
Sign up to set email alerts
|

Optical and geometrical characteristics of cirrus clouds over a Southern European lidar station

Abstract: Abstract. Optical and geometrical characteristics of cirrus clouds over Thessaloniki, Greece (40.6 • N, 22.9 • E) have been determined from the analysis of lidar and radiosonde measurements performed during the period from 2000 to 2006. Cirrus clouds are generally observed in a mid-altitude region ranging from 8.6 to 13 km, with mid-cloud temperatures in the range from −65 • to −38 • C. The cloud thickness generally ranges from 1 to 5 km and 38% of the cases studied have thickness between 2 and 3 km. The retr… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

18
71
2
8

Year Published

2009
2009
2017
2017

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 82 publications
(99 citation statements)
references
References 46 publications
(98 reference statements)
18
71
2
8
Order By: Relevance
“…Recent studies of cloud optical properties have shown the LR frequency distribution is centred at 25 ± 15 sr for ice clouds (Yorks et al, 2011). This value is consistent with other lidar measurements made using this technique (Giannakaki et al, 2007;Immler and Schrems, 2002). In order to have the same confidence in all cases, including thin or thick clouds, and following the literature, we decided to use a constant LR of 25 sr.…”
Section: Ohp Ground-based Lidarsupporting
confidence: 53%
See 2 more Smart Citations
“…Recent studies of cloud optical properties have shown the LR frequency distribution is centred at 25 ± 15 sr for ice clouds (Yorks et al, 2011). This value is consistent with other lidar measurements made using this technique (Giannakaki et al, 2007;Immler and Schrems, 2002). In order to have the same confidence in all cases, including thin or thick clouds, and following the literature, we decided to use a constant LR of 25 sr.…”
Section: Ohp Ground-based Lidarsupporting
confidence: 53%
“…Similar results have been retrieved regarding the variability of Cloud Mean Height which keeps quite constant from one month to another. A mean monthly variation of ∼ 0.15 km around the total mean value has been observed (Sassen and Comstock, 2001), G07 (Giannakaki et al, 2007) and M11 (Min et al, 2011 9.28 ± 1.77 9.4 ± 1.76 8.85 ± 1.95 9.35 ± 1.47 8.17 ± 1.95 9 ± 1.1 9.16 ± 1.83 CTH [km] 10.94 ± 1.68 11.03 ± 1.84 10.4 ± 1.62 10.91 ± 1.48 10.97 ± 1.92 11.7 ± 0.9 10.77 ± 0.9 CT [km] 1.64 ± 1.1 1.64 ± 1.1 1.56 ± 1 1.56 ± 1 2.79 ± 1.38 2.7 ± 0.9 1.6 ± 1.15 for the class 1 and 3 from both CALIOP and the OHP lidar, and of ∼ 0.3 km for the class 2. Parameters for class 2 cirrus clouds agree well with results from G07.…”
Section: Macrophysical Propertiesmentioning
confidence: 99%
See 1 more Smart Citation
“…Only rarely do they contain supercooled liquid cloud droplets at their lower altitudes . Cirrus affects the climate of the whole Earth via two opposite effects; an infrared greenhouse effect and a solar albedo effect (Giannakaki et al, 2007). The contribution of each effect depends strongly on cirrus optical properties (Zerefos et al, 10 2003).…”
Section: Introductionmentioning
confidence: 99%
“…A different technique called 'transmittance method' to determine the optical depth of cirrus clouds from elastic lidar signal has also been developed. It is based on the comparison of the backscattering signals below and above the cloud with assuming that the lidar signals correctly represented the scattering medium (Elouragini and Flamant, 1996;Chen et al, 2002;Giannakaki et al, 2007).…”
Section: Introductionmentioning
confidence: 99%